JADIDS AND THEIR ROLE IN THE NATIONAL AWAKENING OF UZBEKISTAN (Web of Teachers: Inderscience Research, 2026)
This article discusses the Jadid movement and its important role in the national awakening of Uzbekistan and Turkestan in the late nineteenth and early twentieth centuries. The article analyzes the educational, cultural, literary, and political activities of the Jadids, their efforts to modernize society, establish new-method schools, develop the national press, and promote enlightenment among the people. Special attention is given to the contributions of prominent Jadid intellectuals such as Mahmudhoja Behbudi, Abdulla Avloni, Abdurauf Fitrat, and Cho‘lpon. The article also examines the historical significance of the Jadid movement in shaping national identity, educational reform, and independence ideas.